Expert System for the Prevention of Occupational Risks in Construction - Residential Buildings - Hurtado, Gustavo (2022)
Construction companies consider it a priority to prevent occupational accidents and diseases, despite this, accidents in this sector prevail. This study presents OHSYS, an expert system specialized in the prevention of occupational safety in the construction of residential buildings, which evaluates a building project and it is recommended to security officer, actions to mitigate occupational risks. The results show that the number of recommendations increases on average by 7 and 13 for OSH levels of 90% and 100% when using OHSYS. In addition, the satisfaction, usability, and efficiency survey applied to 10 experts show that OHSYS has a very high score (4.5 out of 5).